Green Human Resource Management and Organizational Sustainability: A Systematic Literature Review of Emerging Trends, Determinants, and Implications - Tritisari, Angga; Ramadania, Ramadania (International Journal of Multidisciplinary Sciences and Arts, 2025)
Organizations must incorporate ecological values into their human resource management strategies due to the growing environmental crisis and the global commitment to sustainable development. In order to drive corporate sustainability performance holistically, green human resource management, or GHRM, has become a critical strategic imperative. Using a Systematic Literature Review (SLR) approach, this study attempts to map and synthesize the development trends, determinants, and results of GHRM implementation. For eighteen peer-reviewed journal articles published between 2020 and 2025, the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines were strictly followed during the review process. According to the synthesis results, green hiring, environmental training, and environmentally-based performance reviews are examples of GHRM practices that consistently show a positive and significant impact on organizational sustainability. Internal elements like Organizational Green Culture (OGC) and Green Innovation (GI) played a major role in mediating this influence. The results demonstrated that GHRM is a successful strategic bridge that enhances social and environmental performance, boosts organizational competitiveness, and raises employee affective commitment and job satisfaction. A strong HRM system and support from Green Transformational Leadership are important antecedent factors that drive GHRM success. The majority of previous research uses cross-sectional designs and concentrates on Asian contexts. In order to more thoroughly confirm causal relationships and guarantee the generalizability of results, this gap emphasizes the necessity of future longitudinal research and cross-cultural or cross-industry comparative studies. All things considered, GHRM is a vital tool for contemporary businesses to strike a balance between financial success and environmental responsibility.